A referral pathway for stoma patients. (13th January 2022) - Roberts, Alison
Abstract : Alison Roberts, Nurse Team Leader, Respond Healthcare (alison.roberts@respond.co.uk ) was a runner-up in the Stoma Nurse of the Year category of the British Journal of Nursing Awards 2021